The influence of pH on the liquid-phase transformation of phenolic compounds driven by nitrite photolysis: Implications for characteristics, products and cytotoxicity - Yiran Wang; Min Cai; Yuchen Wang; Weicheng Zhao; Boxuan Wang; Gehui Wang; Xingru Li (Science of The Total Environment, 2024)

Triple-crosslinked double-network alginate/dextran/dendrimer hydrogel with tunable mechanical and adhesive properties: A potential candidate for sutureless keratoplasty - Wen Zhang; Shujing Liu; Lixiang Wang; Boxuan Li; Mengzhen Xie; Yingping Deng; Jialuo Zhang; Huazhang Zeng; Li Qiu; Lisha Huang; Tao Gou; Xiaobo Cen; et al. (Carbohydrate Polymers, 2024)

Intertwined role of mechanism identification by DFT-XAFS and engineering considerations in the evolution of P adsorbents - Ruining Zhao; Benhang Li; Siyuan Chen; Boxuan Zhang; Jiale Chen; Jiahe Sun; Xiaodong Ma (Science of The Total Environment, 2024)

21Ne and 10Be dating of folded fluvial terraces: Constraining active deformation of the Guman fold along the foothill of the western Kunlun mountains (Xinjiang, China) - Jianhong Xu; Jie Chen; Tao Li; Boxuan Zhang; Ning Di; Wei Pang (Journal of Structural Geology, 2024)

Microplastic co-exposure elevates cadmium accumulation in mouse tissue after rice consumption: Mechanisms and health implications - Shan Chen; Haijun Gan; Xinying Lin; Boxuan Wang; Mengya Li; Lena Q. Ma; Dongmei Zhou; Hongbo Li (Journal of Hazardous Materials, 2024)

Simultaneous nitrification and denitrification in a hybrid activated sludge-membrane aerated biofilm reactor (H-MABR) for nitrogen removal from low COD/N interflow: A pilot-scale study - Hengyi Liu; Lei Li; Wenjie Ye; Boxuan Zhao; Yun Peng; Guotao Liu; Xiaofeng Gao; Xuya Peng (Journal of Environmental Management, 2024)

Rapid Rescue of Goose Astrovirus Genome via Red/ET Assembly - Daqing Cui; Shujun Li; Boxuan Yin; Changyan Li; Lilin Zhang; Zexing Li; Jinhai Huang (Food and Environmental Virology, 2024)

Natural mineral and industrial solid waste-based adsorbent for perfluorooctanoic acid and perfluorooctane sulfonate removal from surface water: Advances and prospects - Siyuan Chen; Benhang Li; Ruining Zhao; Boxuan Zhang; Yuqing Zhang; Jiale Chen; Jiahe Sun; Xiaodong Ma (Chemosphere, 2024)

Impacts and influencing pathways of urbanization on carbon–water-energy-food nexus across Chinese cities - Chenggang Li; Yong Liu; Zhenci Xu; Gang Zhao; Youhui Bao; Chengcheng Cai; Yu Lu; Yufeng Mao; Alexander Boxuan Wang; Liang Wu (Environment, Development and Sustainability, 2024)
Food, water, energy and carbon (F-W-E-C), as important factors of urban development, have synergistic effects and trade-off effects with each other. Scientifically assessing the impact of urbanization on the F-W-E-C nexus is beneficial to optimize the urban development layout and achieve the sustainable urban development. Nevertheless, extant studies have not evaluated the impact and influencing pathways of urbanization on the F-W-E-C nexus. In this study, the Coupling Coordination Degree Model is used to explore the F-W-E-C nexus of 252 prefecture-level cities in China. The panel data model and mediating effect model are utilized to study the impact of urbanization on the F-W-E-C nexus and the impact pathways. This study finds that the F-W-E-C nexus across Chinese cities is weak trade-off. The urbanization promotes the synergy of F-W-E-C. The positive impact is greater in the central cities than in the eastern and western cities, and is greater in medium-sized cities than in small cities, large cities and above. The technological progress is an important pathway of urbanization impacting the F-W-E-C nexus, and assists urbanization to generate a positive influence on the F-W-E-C nexus. This research has implications for promoting a systematic, orderly, and rational coordination development of F-W-E-C and for sustainable urbanization development in China and the world.

Gender-specific effects of polystyrene nanoplastic exposure on triclosan-induced reproductive toxicity in zebrafish (Danio rerio) - Zhiming Li; Hongyi Xian; Rongyi Ye; Yizhou Zhong; Boxuan Liang; Yuji Huang; Mingzhu Dai; Jie Guo; Shuqin Tang; Xiaohu Ren; Ruobing Bai; Yu Feng; et al. (Science of The Total Environment, 2024)

From cradle to grave: Deciphering sex-specific disruptions of the nervous and reproductive systems through interactions of 4-methylbenzylidene camphor and nanoplastics in adult zebrafish - Hongyi Xian; Zhiming Li; Ruobing Bai; Rongyi Ye; Yu Feng; Yizhou Zhong; Boxuan Liang; Yuji Huang; Jie Guo; Binjie Wang; Mingzhu Dai; Shuqin Tang; et al. (Journal of Hazardous Materials, 2024)

Cost-effectiveness of latent tuberculosis infection testing and treatment with 6-week regimen among key population in rural communities in China: a decision analysis study - Xuefang Cao; Tonglei Guo; Henan Xin; Jiang Du; Chenlu Yang; Boxuan Feng; Yijun He; Lingyu Shen; Yuanzhi Di; Zihan Li; Yanxiao Chen; Jianguo Liang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Revealing new insights: Two-center evidence of microplastics in human vitreous humor and their implications for ocular health - Yizhou Zhong; Yuhang Yang; Linan Zhang; Dahui Ma; Kailiang Wen; Jiachun Cai; Zhanmou Cai; Cui Wang; Xiaoyan Chai; Jingwen Zhong; Boxuan Liang; Yuji Huang; et al. (Science of The Total Environment, 2024)

Vertically designed high-performance and flexible thermoelectric generator based on optimized PEDOT:PSS/SWCNTs composite films - Binjie Xia; Xiao-Lei Shi; Li Zhang; Jia Luo; Wen-Yi Chen; Boxuan Hu; Tianyi Cao; Ting Wu; Wei-Di Liu; Yanling Yang; Qingfeng Liu; Zhi-Gang Chen (Chemical Engineering Journal, 2024)

Seasonal variations of microplastics in surface water and sediment in an inland river drinking water source in southern China - Wenyu Zhao; Jing Li; Mengyue Liu; Rui Wang; Boxuan Zhang; Xiang-Zhou Meng; Shengwei Zhang (Science of The Total Environment, 2024)